A scoping review of medical professionalism research published in the Chinese language. Issue 1 (December 2016) - Wang, Xin; Shih, Julie; Kuo, Fen-Ju; Ho, Ming-Jung
Abstract Background The Chinese Medical Doctors Association (CMDA) adopted the Charter of Medical Professionalism in the New Millennium (Charter) and published the Chinese Medical Doctor Declaration (Declaration). This is an important step to re-building medical professionalism in China at a time when the commercialization of health care has led to a decline in physician accountability and public trust in the profession. In response, authors have begun to examine and promote medical professionalism in China. This study aims to present the key research themes, identify research gaps and offer recommendations from reviewing the increasing pool of Chinese-language literature on medical professionalism. Methods A scoping review of Chinese language papers was conducted using the China National Knowledge Infrastructure (including China Academic Journals Full-text Database, China Doctoral Dissertations Full-text Database, Masters' Theses Full-text Database, China Core Newspapers Full-text Database, and China Yearbooks Full-text Database) (CNKI) database. Results Four major research themes were identified in Chinese discourse: (1) teaching professionalism, (2) practicing professionalism, (3) conceptualizing professionalism and (4) assessing professionalism. Overall, authors were concerned with the cultivation of humanism in physicians and emphasized the importance of communication skills to improve the physician-patient relationship in China. They explored the role of traditional Chinese values, such as Confucian and Taoist values, as well as the Communist Party's political values, in promoting professional behaviour. Conclusions Authors demonstrate increasing interest in medical professionalism in China. The literature is of variable quality and further empirical studies are required in order to evaluate teaching interventions and guide professionalism assessment. A common professionalism framework is absent and could be developed with consideration to China's socio-cultural context.